2013
DOI: 10.1175/jas-d-12-0227.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Explicit versus Parameterized Convection on the MJO in a Large-Domain High-Resolution Tropical Case Study. Part I: Characterization of Large-Scale Organization and Propagation*

Abstract: High-resolution simulations over a large tropical domain (;208S-208N, 428E-1808) using both explicit and parameterized convection are analyzed and compared to observations during a 10-day case study of an active Madden-Julian oscillation (MJO) event. The parameterized convection model simulations at both 40-and 12-km grid spacing have a very weak MJO signal and little eastward propagation. A 4-km explicit convection simulation using Smagorinsky subgrid mixing in the vertical and horizontal dimensions exhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
125
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(138 citation statements)
references
References 58 publications
(56 reference statements)
12
125
1
Order By: Relevance
“…Hsu and Li (2012) found that the BL convergence-induced moistening to the east of MJO convection is a primary cause for the MJO eastward propagation, while the BL convergence is related to the heating-induced free atmosphere wave dynamics. The second mechanism is stratiform cloud-wave interaction (Mapes 2000;Khouider and Majda 2006;Kuang 2008;Fu and Wang 2009;Seo and Wang 2010;Holloway et al 2013). Fu and Wang (2009) and Seo and Wang (2010) showed that the latent heating released in stratiform clouds produces MJO eddy available potential energy (EAPE), which allows direct interaction between heating and largescale circulation and sustains the MJO.…”
Section: Introductionmentioning
confidence: 99%
“…Hsu and Li (2012) found that the BL convergence-induced moistening to the east of MJO convection is a primary cause for the MJO eastward propagation, while the BL convergence is related to the heating-induced free atmosphere wave dynamics. The second mechanism is stratiform cloud-wave interaction (Mapes 2000;Khouider and Majda 2006;Kuang 2008;Fu and Wang 2009;Seo and Wang 2010;Holloway et al 2013). Fu and Wang (2009) and Seo and Wang (2010) showed that the latent heating released in stratiform clouds produces MJO eddy available potential energy (EAPE), which allows direct interaction between heating and largescale circulation and sustains the MJO.…”
Section: Introductionmentioning
confidence: 99%
“…Given moisture's central role, it is not surprising that some improvements can also be found by altering the moistening tendencies of convection, for example, by increasing the amount of evaporation of convective rain [Maloney, 2009;Del Genio et al, 2012]. While model resolution does not consistently impact a simulated MJO [Crueger et al, 2012;Holloway et al, 2013], an interactive ocean usually improves the MJO simulation [Waliser et al, 1999;Sperber et al, 2005;Woolnough et al, 2007;X. Jiang et al, submitted manuscript, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to theoretical modeling, various processes and mechanisms have been identified or speculated to play significant roles in MJO dynamics based on numerical model experiences and observations, including shallow convection-BL circulation interaction (Johnson et al 1999;Kikuchi and Takayabu 2004;; stratiform cloud-wave interaction (Mapes 2000;Khouider and Majda 2006;Kuang 2008;Fu and Wang 2009;Seo and Wang 2010;Holloway et al 2013); cloud-radiation interaction (Lee et al 2001;Raymond 2001;Bony and Emanuel 2005;Andersen and Kuang 2012); moisture-convection feedback (Woolnough et al 2001;Grabowski and Moncrieff 2004;Benedict et al 2014), and moisture transport (Maloney 2009;Maloney et al 2010;Andersen and Kuang 2012;Hsu and Li 2012;Kim et al 2014;Pritchard and Bretherton 2014). More details were reviewed by Zhang (2005) and Wang (2005Wang ( , 2012.…”
mentioning
confidence: 99%